Viper Venom and Synthetic Peptides: Emerging Active Ingredients in Anti-Ageing Cosmeceuticals - Dana Georgiana Moisă; Anca Maria Juncan; Luca-Liviu Rus; Andreea Loredana Vonica-Țincu; Gabriela Cormoș; Felicia Gabriela Gligor (Applied Sciences)
The animal kingdom, particularly reptiles, is widely recognized as a valuable source of peptides and proteins with applications in medicine, the pharmaceutical industry and, more recently, the cosmetic industry. This prompted an investigation into the prevalence of cosmetic products utilizing synthetic peptides, with a specific focus on viper venom. A major objective of our study was a comparative analysis between natural venom-derived peptides and synthetic analogues, which could provide valuable insights into the market impact. The identification and inclusion of these products were based on their listings according to the International Nomenclature of Cosmetic Ingredients (INCI), alongside a review of the current literature and the recognition of relevant studies aimed at evaluating the composition of viper venom. Additionally, cosmetics were identified through online media using specific keywords such as “viper venom”, “snake venom”, “snake”, “SYN®-AKE”, “analogues of snake venom” or “synthetic snake venom”, followed by a comparative analysis of the products identified. The study provided an extensive background considering the market segmentation of viper venom-based and synthetic peptide-based cosmetics, including 245 cosmetics (70 manufacturers), also including the classification into Mass-Market and Premium-Market segments, which adds practical value. In 81% of the total analyzed products, the synthetic analogue was present, SYN®-AKE (INCI Dipeptide Diaminobutyroyl Benzylamide Diacetate (and) Glycerin (and) Aqua), while 13% contained snake venom or viper venom. The high percentage of cosmetics categorized under the Mass-Market segment could be attributed to the use of synthetic peptides, given the high cost of natural viper venom as an anti-ageing ingredient, a price likely reflected in the final cosmetic product. In terms of product category, skin care cosmetics made up the largest share, followed by body care products, typically claiming anti-ageing and moisturizing properties.